PENGARUH PELAYANAN TELEKONSULTASI TERHADAP KEPUASAN PASIEN DI KLINIK JIWA MASAGI MEDIKA BANDUNG - Ariani, Nurul Dwi; Phang, Lisa (Jurnal Infokes, 2022)
The purpose of this study was to determine the effect of teleconsultation services on patient satisfaction at the Masagi Medika Mental Clinic in Bandung. This research method uses a quantitative method with a descriptive approach. The data collection technique used is by conduting samples, questionnaries, observations and literature studies which have a close relevance to the main problem in the research. The result showed that the influence of teleconsultation services on patient satisfaction at the Mental Clinic Medika Banding was 72% and the remaining 28% was influened by other factors or errors. The problems contained in the Effect of Teleconsultation Services on Patient Satisfaction at the Masagi Medika Mental Clinic in Bandung are : (1) Teleconsultation using via zoom causes elderly patients to be constrained when using teleconsultation applications, (2) The duration of the teleconsultation is too little resulting in less flexibility durig examinations. Suggestions given to overcome the problems that occur are : (1) It is recommended to use an automated system facility for examination of patients so as to minimize errors in using the zoom application, especially in elderly patients, (2) Use an application that provides enough time such as a paid application zoom so that during the examination to provide comfort to the patient during the consultation. Keywords : Teleconsultation Services, Patient Satisfaction.